First in-situ use of a mobile CT-scan for museum artefacts: The quai Branly – Jacques Chirac museum experience. (March 2020) - Charlier, P.; Kissel, E.; Moulherat, C.; Kimmel, P.A.; Le Fur, Y.; Fontaine, M.A.; Veynachter, M.; Jacqueline, S.; Deo, S.; Huynh, I.; Gorincour, G.
Highlights: CT-scan is currently used for museum artefacts analyses. Here we show the feasibility and interest of a large-scale in-situ examination. Methodology, results and perspective are given here. Abstract: Background: Radiology has many uses other than clinical diagnosis or surgical planning. In museum settings, the use of X-rays is frequent for objects submitted to structural analysis (in that case, they are temporarily moved to hospitals or research centers for this special exam). Purpose: For the first time, we wanted to test the feasibility of a CT-scan (computed tomography) in-situ, i.e. in an international museum setting, with the help of a mobile CT-scan device. Results: Here we present the results of our study carried out at the quai Branly – Jacques Chirac museum (Paris, France) carried out on nearly 150 extra-european artifacts. Our study shows not only the feasibility of such a large-scale non-invasive CT-scan examination in a museum, but also the growing need for such an examination that opens the way to a new disciplinary field for radiology: CT-scan will become almost indispensable and systematic in museum research centers.